Характер успадкування морфологічних ознак колоса у гібридів Triticum spelta × Triticum aestivum - Січкар, С.М.; Моргун, В.В.; Дубровна, О.В. (Фактори експериментальної еволюції організмів, 2016)
Aim. The nature of inheritance of morphological traits in simple and backcross hybrids F1 and F2 of spelt with bread wheat was investigated. Methods. Field and laboratory methods for studying the inheritance of morphological characteristics in hybrids F1 and F2 . Results. It was confirmed that for simple hybrids of different wheat species, the morphological characteristics of plants, including spike shape, hull, spinous and plant height inherited monogenic. Additive effect of spelt and wheat genes, which determine the spikelet number, leading to its significant increase in ear was discovered. In backcross hybrids, with domination of the genome of other wheat species, the deviation from the theoretically expected traits splitting was observed. Conclusions. It was established that the increase in the number of spelt genes in the backcross hybrid increases the differences with wheat and make values of spike characteristics closer to the spelt. Keywords: Triticum spelta L., T. aestivum L., morphological characteristics, genetic analysis.